High-Throughput MALDI-TOF Discovery of Genomic Sequence Polymorphisms - Stanssens, Patrick; Zabeau, Marc; Meersseman, Geert; Remes, Gwen; Gansemans, Yannick; Storm, Niels; Hartmer, Ralf; Honisch, Christiane; Rodi, Charles P.; Böcker, Sebastian; van den Boom, Dirk (Genome Research, 2004)
We describe a comparative sequencing strategy that is based on matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) analyses of complete base-specific cleavage reactions of a target sequence. The target is converted to a DNA/RNA mosaic structure after PCR amplification using in vitro transcription. Cleavage with defined specificity is achieved by ribonucleases. The set of cleavage products is subjected to mass spectrometry without prior fractionation. The presented resequencing assay is particularly useful for single-nucleotide polymorphism (SNP) discovery. The combination of mass spectra from four complementary cleavage reactions detects approximately 98% of all possible homozygous and heterozygous SNPs in target sequences with a length of up to 500 bases. In general, both the identity and location of the sequence variation are determined. This was exemplified by the discovery of SNPs in the human gene coding for the cholesteryl ester transfer protein using a panel of 96 genomic DNAs.